A screening instrument for side dominance in competitive adolescent alpine skiers - Westin, Maria; Norlén, Annelie; Harringe, Marita L.; Werner, Suzanne (Frontiers in Sports and Active Living, 2022)
Previous research has shown that ski high school students injure their left anterior cruciate ligament (ACL) more often than their right ACL and that a prevention program focusing on equal load to the right and left ski turn prevents ACL injuries. Whether the injuries were in the dominant or non-dominant side of the ski students was not determined, but may be important knowledge to ski coaches for future design of ski specific training programs. There is no gold standard on how to investigate dominant side in alpine skiers. Therefor the aim of the present study was to develop a screening instrument consisting of five questions for identifying side dominance and to evaluate side dominance in competitive adolescent alpine skiers. Firstly, 121 competitive adolescent alpine skiers answered the questions of side dominance using a test-retest design. The questions were; what hand/arm (left/right) or foot/leg (left/right) that one uses as the first choice when writing, throwing, kicking a ball, jumping over a fence and stair climbing. A question of a safer/better ski turn to the left or to the right was also added. Secondly, 274 skiers answered the questions at one occasion. A very good agreement was shown in writing, throwing and kicking a ball and a fair agreement in jumping over a fence and stair climbing. 243 skiers reported a right sided dominance and seven skiers a left sided dominance. One hundred and nineteen of the 121 skiers who took part in the test-retest design answered the question safer/ better ski turn, and of those 70 skiers (59%) reported that they had a safer/better ski turn to one side compared to the other side. However, the side was not consistent between the two test occasions and the question did not correlate with side dominance. A combination of the questions “what hand/arm or foot/leg do you use as first choice when writing, throwing and kicking a ball” may be used to decide side-dominance in adolescent alpine skiers. Most adolescent alpine skiers reported a right sided dominance.